2015
DOI: 10.1016/j.anucene.2015.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Pressure oscillation and steam cavity during the condensation of a submerged steam jet

Abstract: a b s t r a c tSteam jet condensation is important in many industrial applications. In this work, the pressure oscillation and steam jet patterns during submerged jet condensation in quiescent water is investigated experimentally. Firstly, it is found that even at stable condensation region, the steam cavity length varies all the time and steam bubbles separate from the steam cavity periodically. With the variation of steam cavity length and separated bubble oscillation, condensation also undergoes oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The oscillation power comparisons of the first and the second frequency bands revealed that, under the test condition, when air mass fraction increases from A=0% to A=5%, the maximum oscillation power of the second frequency band is always higher than that of the first frequency band, as shown in figure 17. This finding is similar to the results reported by Zhao et al(2015). However, after A>1%, the oscillation power gap between the two frequency bands decreases with the rise of air mass fraction.…”
Section: Oscillation Powersupporting
confidence: 91%
See 3 more Smart Citations
“…The oscillation power comparisons of the first and the second frequency bands revealed that, under the test condition, when air mass fraction increases from A=0% to A=5%, the maximum oscillation power of the second frequency band is always higher than that of the first frequency band, as shown in figure 17. This finding is similar to the results reported by Zhao et al(2015). However, after A>1%, the oscillation power gap between the two frequency bands decreases with the rise of air mass fraction.…”
Section: Oscillation Powersupporting
confidence: 91%
“…The axial position of the oscillation peak also moves downstream gradually with rise of air mass fraction. As reported by Zhao et al (2015), the oscillation intensity peak is located at the end of the steam cavity. When air mass fraction increases, heat transfer coefficient of the steam-water interface decreases considerably (Choi et al, 2002;Liang and Griffith, 1994).…”
Section: Condensation Oscillation Intensitysupporting
confidence: 61%
See 2 more Smart Citations
“…Besides the first domain frequency, the second dominant frequency was found under certain test conditions [19]. Zhao et al [20] investigated the distribution of pressure oscillation intensity and found that its peak at the steam plume tail. Chong et al [21] released that the second dominant frequency was caused by separated steam bubbles.…”
Section: Introductionmentioning
confidence: 99%